The transition from LHIIIB2 to LHIIIC and Sub Mycenaean in Achaia - Jolliffe, Amy (2017)
This work constitutes a comprehensive study of Late Helladic IIIC and Submycenaean Achaia, examining continuity and change after the upheaval of the collapse of the palaces in c.1200BC. The aim of this thesis is to examine Achaia’s changing role, and whether this could be directly related to, or affected by, the collapse of the Mycenaean palaces. This research attempts to determine how power and influence shifted and flowed throughout the region at the time, and how trade and exchange may have changed across the Aegean. During the upheavals of the LH IIIC period, new sites emerged, and it is worth considering why these sites became important during this period. The LH IIIC period in particular is thought to have been one of prosperity for Achaia, perhaps in part due to the ability of the region being able to control some seaways (e.g. the Ionian Sea), and this resulted in Achaia being susceptible to influences coming from overseas – as shall be explored through the material culture. I will seek to examine the wider context of Achaia’s position in relation to the Aegean. Scholarly interest has suggested that the aforementioned disruptions were not a global phenomenon, but rather occurred within a regional pattern of local trade routes. By reassessing the material culture from these areas, we could potentially chart the development of trade and exchange relations. The material culture (including pottery and metal finds) from various habitation sites and cemeteries, and the evidence from the so-called ‘warrior graves’, will form the basis of my analysis and interpretation. The importance of this research lies in the fact that this area had only been sporadically studied, and it is only recently that archaeological scholarship has started to consider it alongside the core regions of the Mycenaean world. Thus it is time for a reassessment of the region.